Factors Affecting Career Progress of MBA Students - Supangco, Vivien T. (Social Science Diliman: A Philippine Journal of Society and Change; Vol 2 No 1 (2001), 2007)
This paper explored the factors that affect career progress of students in the MBA program of the University of the Philippines. To understand career progression, four measures of career progress were used in this study, namely: number of promotions, number of years in between promotions, total cash compensation, and number of administrative levels from the company president. On the other hand, the factors used to explain career progess included human capital, organizational, interpersonal and demographic variables. The results showed that the different measures of career progress had distinct determinants implying different dynamics. It appeared that measures of career progress that are sensitive to the value employers attach to the individual (Whitely, Dougherty, & Dreher, 1991) such as total compensation, total number of promotion and years per promotion were related with human capital factors such as work experience and number of companies worked for. On the other hand, measures that relate to centrality if the position, in which market forces have less impact, were associated with organizational variables such as organization size and the demographic variable gender. While gender did not explain variation in total compensation, number of promotions and number of uears between promotions, these null results are important for two reasons. First, it implies that the female MBA students were at par with their male counterparts as fas as these measures of career progress are concerned. Second, it challenges the generalizability of the finding of gender segregation at the organizational level-where men receive significantly higher wages that women-which is a common finding among studies done in the United States. The results using the MBA students as sample show that income and promotion parity may indeed be achievable and this brings hope to women in general. However, the statistical significance of gender in explaining career progress as centrality of position does not augur well for women. This result implies that despite the fact that the women in the sample were intelligent (that is, they passed the stringent MBA screening), motivated and obviously were able to manage their time well-being able to balance work, school and in some cases, family responsibilities-they were still far removed from the top. These women still faced some hostile environment that prevented them from fully contributing to making decisions that matter.